Extrapontine Myelinolysis following Extreme Hypernatremia and Hyperosmolarity - Jan-Niclas Schwade (Case Reports in Pediatrics, 2019)
We present a case of a nearly 3-year-old girl who was admitted to hospital due to severe hypernatremia (196 mmol/l). Her medical history included central hypothyreosis and growth hormone deficiency. Rehydration and normalization of sodium was achieved according to guidelines. On the fourth day of hospitalization, the patient developed tremor, ataxia, and rigor. Cranial magnetic resonance imaging (cMRI) was performed and (mis)interpreted for meningoencephalitis, with corresponding diagnostic and therapeutic implications. The patient had extrapontine myelinolysis. The child recovered completely after hospitalization for nearly 2 weeks.